The nature of management : a text for professionals - Agbato, Joe Ona. (Lagos, Nigeria : Joe Ona Agbato, 1982)
The book caters for the educational and professional needs of those in the school of management and banking in Nigeria.
Includes bibliographical references and index.
oif 05/03/2019
Loans
Keywords: Management; Industrial management